Sixteen-year experience with aortic root replacement. Results of 172 operations. - Kouchoukos, N T (1991)
During a 16-year interval ending in October 1990, 168 patients underwent 172 aortic root replacements. Thirty patients (18%) had Marfan syndrome. Annuloaortic ectasia (81 patients) and aortic dissection (63 patients) were the principal indications for operation. Twenty-seven patients (16%) had previous operations on the ascending aorta or aortic valve. The hospital mortality rate was 5% and the duration of cardiopulmonary bypass was the only significant independent predictor of early death (p = 0.017). Major modifications in technique were made in 1981, when the inclusion/wrap technique employing a composite graft (used in the first 105 procedures) was abandoned in favor of an open technique (used in 51 procedures), and in 1988, when aortic allografts and pulmonary autografts were introduced for selected conditions (reoperations, dissection, endocarditis, isolated aortic valve disease) in 16 patients. The mean duration of follow-up was 81 months. Forty-six patients were followed for more than 10 years. The actuarial survival rate was 61% at 7 years and 48% at 12 years. No significant difference in survival rate was observed between the patients with annuloaortic ectasia and aortic dissection, or between the inclusion/wrap and open techniques. However the frequency of pseudoaneurysm formation at suture lines and the frequency of reoperations on the ascending aorta and aortic valve were less with the open technique. The actuarial freedom from thromboembolism for the 152 patients with prosthetic valves was 82% at 12 years. One early and one late death occurred among the 16 patients with allograft or autograft root replacement. Anticoagulant therapy was not used in these patients and no thromboembolic episodes occurred in the follow-up period (mean, 7 months). The satisfactory results observed with extended follow-up support the continued use of the composite graft technique as the preferred method of treatment for patients with annuloaortic ectasia, persistent aneurysms of the sinuses of Valsalva following previous operations, and for patients with ascending aortic dissection who require aortic valve replacement. The availability of aortic root allografts and the perfection of techniques for safe implantation of the autologous pulmonary root into the aortic position have broadened the indications for aortic root replacement.